Advancements in Gel Science-A Special Issue in Memory of Toyoichi Tanaka - Tokita, Masayuki (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
A gel is a state of matter that consists of a three-dimensional cross-linked polymer network and a large amount of solvent. Because of their structural characteristics, gels play important roles in science and technology. The science of gels has attracted much attention since the discovery of the volume phase transition by Professor Toyoichi Tanala at MIT in 1978. MDPI planned to publish a Special Issue in Gels to celebrate the 40th anniversary of this discovery, which received submissions of 13 original papers and one review from various areas of science. We believe that readers will find this Special Issue informative as to the recent advancements of gel research and the broad background of gel science.